Dauphine diplomacy Marie-Josèphe of Saxony towards French policy in the mid-18th century - Kuras, Katarzyna (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
The article presents „the secret of Dauphine of France”, i.e. the actions taken by Marie-Josephe of Saxony (1731–1767), the wife of Dauphin of France Louis Ferdinand, to bring her brother, Prince Francis Xavier de Saxony, to the Polish throne. The „secret” reconstructed in works published between 1901 and 1902 by Casimir Stryienski occupies a marginal but permanent place in the historiography literature. In the light of this analysis, which takes into account the legal and traditional position of Dauphine at the French court, the foreign policy of France in Central and Eastern Europe in the middle of the 18th century, and the knowledge that Maria Józefa possessed on the realities of the Polish policies, it turns out that the „secret” in its current version was an exaggerated, literary construct rather than a diplomatic reality.